A Consistent Routing Protocol Based On Graph Theory For Efficient Vehicle To Vehicle Communication - Vigilia, A. Navis; Suseela, J. Suresh (International Journal of Computer Sciences and Engineering, 2018)
Vehicular Ad-hoc Networks (VANETs) are made exclusive for vehicular communications in which each node makes a bidirectional connectivity with other nodes. VANET has attracted more researchers and has unlocked a track to cultivate few applications like propagation of travel alerts, traffic status, and user defined applications. Each node in VANET has some unique features like dynamic network structure, high mobility, low processing speed and low memory. These features make VANET unique and different from other wireless networks. These features need a special attention, while designing a routing protocol to VANETs. This paper proposes a novel consistent routing protocol called CRP for inter vehicular communications to achieve a consistent and reliable route between the source and destination. Based on link reliability value and graph traversals, a source node predicts a reliable path among the neighboring nodes. The proposed algorithm is designed to work in a stressful urban environment and significantly outperforms than the other existing algorithms.